Bisavenathramide Analogues as Nrf2 Inductors and Neuroprotectors in In Vitro Models of Oxidative Stress and Hyperphosphorylation - Ángel Cores; Sheila Abril; Patrycja Michalska; Pablo Duarte; Ana I. Olives; M. Antonia Martín; Mercedes Villacampa; Rafael León; J. Carlos Menéndez (MDPI AG, 2021)
Oxidative stress is crucial to the outbreak and advancement of neurodegenerative diseases and is a common factor to many of them. We describe the synthesis of a library of derivatives of the 4-arylmethylen-2-pyrrolin-5-one framework by sequential application of a three-component reaction of primary amines, β-dicarbonyl compounds, and α-haloketones and a Knoevenagel condensation. These compounds can be viewed as cyclic amides of caffeic and ferulic acids, and are also structurally related to the bisavenanthramide family of natural antioxidants. Most members of the library showed low cytotoxicity and good activity as inductors of Nrf2, a transcription factor that acts as the master regulator of the antioxidant response associated with activation of the antioxidant response element (ARE). Nrf2-dependent protein expression was also proved by the significant increase in the levels of the HMOX1 and NQO1 proteins. Some compounds exerted neuroprotective properties in oxidative stress situations, such as rotenone/oligomycin-induced toxicity, and also against protein hyperphosphorylation induced by the phosphatase inhibitor okadaic acid. Compound 3i, which can be considered a good candidate for further hit-to-lead development against neurodegenerative diseases due to its well-balanced multitarget profile, was further characterized by proving its ability to reduce phosphorylated Tau levels.